Brain connectivity disruptions in PTSD related to early adversity: a multimodal neuroimaging study - Nkrumah, Richard O.; Demirakça, Traute; Schröder, Claudius von; Zehirlioğlu, Lemye; Valencia, Noel; Grauduszus, Yasmin; Vollstädt-Klein, Sabine; Schmahl, Christian; Ende, Gabriele (European journal of psychotraumatology, 2024)
Background: Post-traumatic stress disorder (PTSD) is increasingly prevalent in individuals with adverse childhood experiences (ACE). However, the underlying neurobiology of ACE-related PTSD remains unclear. Objective: The present study investigated the brain connectivity in ACE-related PTSD using multimodal neuroimaging data. Methods: Using a total of 119 participants with ACE (70 with ACE-related PTSD and 49 ACE-exposed controls), this study acquired T1-weighted MRI, diffusion-weighted MRI, and resting-state fMRI data to examine structural and functional connectivity between groups. Joint connectivity matrix independent component analysis (Jcm-ICA) was employed to allow shared information from all modalities to be examined and assess structural and functional connectivity differences between groups. Results: Jcm-ICA revealed distinct connectivity alterations in key brain regions involved in cognitive control, self-referential processing, and social behaviour. Compared to controls, the PTSD group exhibited functional hyperconnectivity of the right medial prefrontal cortex (PFC) of the default mode network and right inferior temporal cortex, and functional hypoconnectivity in the lateral-PFC of the central executive network and structural hypoconnectivity in white matter pathways including the right orbitofrontal region (OFC) linked to social behaviour. Post-hoc analyses using the joint brain-based information revealed that the severity of ACE, the number of traumas, and PTSD symptoms later in life significantly predicted the effects of ACE-related PTSD on the brain. Notably, no direct association between brain connectivity alterations and PTSD symptoms or the number of traumas within the PTSD group was observed. Conclusion: This study offers novel insights into the neurobiology of ACE-related PTSD using multimodal data fusion. We identified alterations in key brain networks (DMN, CEN) and OFC, suggesting potential deficits in cognitive control and social behaviour alongside heightened emotional processing in individuals with PTSD. Furthermore, our findings highlight the combined influence of ACE exposure, number of traumas experienced, and PTSD severity on brain connectivity disruptions, potentially informing future interventions. In the present study individuals with a history of childhood adversity and PTSD reported distinct alterations in functional and structural connectivity patterns in key brain networks involved in cognitive control, self-referential processing, and social behaviour.Additionally, evidence of brain deficits in the right medial prefrontal cortex, right inferior temporal cortex, lateral PFC and right orbitofrontal cortex in ACE-related PTSD was derived from multimodal brain features.Furthermore, the study demonstrated a potential link between the severity of ACE, the number of traumas, and PTSD symptoms with the observed brain connectivity disruptions.Notably, no direct association between brain connectivity alterations and PTSD symptoms or the number of traumas within the PTSD group was found, suggesting that trauma severity, rather than number of traumas, may play a crucial role in shaping brain structure and function in individuals with PTSD. In the present study individuals with a history of childhood adversity and PTSD reported distinct alterations in functional and structural connectivity patterns in key brain networks involved in cognitive control, self-referential processing, and social behaviour. Additionally, evidence of brain deficits in the right medial prefrontal cortex, right inferior temporal cortex, lateral PFC and right orbitofrontal cortex in ACE-related PTSD was derived from multimodal brain features. Furthermore, the study demonstrated a potential link between the severity of ACE, the number of traumas, and PTSD symptoms with the observed brain connectivity disruptions. Notably, no direct association between brain connectivity alterations and PTSD symptoms or the number of traumas within the PTSD group was found, suggesting that trauma severity, rather than number of traumas, may play a crucial role in shaping brain structure and function in individuals with PTSD.